The Value Relevance of Earnings and Book Values: A Case from Financial Institutions in Indonesia - Hadinata, Sofyan (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2023)
Purpose: This study aims to assess the ﬁeld of the accounting value relevance of earnings and book value on stock prices of banks and ﬁnancial institutions listed in the Indonesia Stock Exchange. Methodology: Using a sample of available banks and ﬁnancial institutions listed in the Indonesia Stock Exchange from 2014 to 2021, this paper accommodates the documented accounting information in an emerging market context by using stock price of four months after year-end as a dependent variable. This study used the panel data regression technique on 31 banks and 36 others ﬁnancial institution during the study period. Findings: This research ﬁnd that earnings and book value are statistically signiﬁcant associated with ﬁrm stock price. Also, using these variables together is positively related to the ﬁrm stock price. Comparatively between banks and financial institutions, these obtain evidence that earnings per share is statistically more value-relevant than book value. Novelty: This research used the financial sector, both banking and other financial institutions, because both types of institutions are intermediary institutions that greatly influence a country's economy.